Panchagvya A solution for well being of plants - Patel, Dahyabhai M. (Indian Farming, 2017)
The traditional practices are followed by farmers in the field from the time immemorial. But humanity was lured by chemical technology and it abandoned the ancient wisdom generated during the past. Vrikshayurveda is a treasure trove of information on agriculture and as such could lend support to organic agriculture; Panchagavya has been one such piece of wisdom, meant to safeguard all the human beings, animals, plants and microorganisms that dwell on the earth’s surface. The Vriskshayurveda systematizes the use of Panchagavya.